"I'm on a journey I never thought I'd be on": using process drama pedagogy for the literacy programme. (3rd April 2017) - Wells, Trish; Sandretto, Susan
ABSTRACT: This paper argues that process drama is a productive pedagogy with multiple affordances for multiliteracies. We describe an exploratory study in which two teachers from a rural New Zealand primary school used process drama pedagogy in the literacy programme. Analysis of the initial and exit teacher interviews, lesson transcripts and transcripts of the teacher-researcher meetings demonstrated the power of using process drama. When the teachers used process drama, we found that students developed their text user, meaning maker and text analyst practices through greater engagement, more detailed writing and an enhanced depth of thinking. Importantly, students who often struggled to make contributions in the class were included. In order to realise the potential of process drama pedagogy for multiliteracies, we found that the teachers needed a great deal of support to build their confidence to use process drama due to their limited professional experiences of the arts. This study encourages further use and exploration of process drama pedagogy for multiliteracies.